Chemical Composition in Essential Oils of Schefflera octophylla L. Harvested in Hai Duong Province, Vietnam - Toan, Tran Quoc; Long, Pham Quoc; Quan, Pham Minh; Kim Gan, Tran Thi; Huyen, Luu Van; Hai Ha, Pham Thi (Asian Journal of Chemistry, 2020)
This study aims to determine the chemical composition of essential oils extracted from Schefflera octophylla L. harvested in Pha Dong commune, Chi Linh district, Hai Duong province, Vietnam. To determine the concentration of volatile components, GC - MS was performed. The results showed that the content of volatile substances occupied 97.07% of essential oils. Some main ingredients having medicinal properties were myrcene (9.0%), cis-β-elemene (6.67%), E-caryophylene (β-caryophylene) (24.91%), α-selinene (6.30%), β-selinene (7.29%). This study opens new potentials in the application of chemical ingredients in the fields of pharmaceuticals, cosmetics, agriculture and in some therapeutic activities.